2019
DOI: 10.1111/jop.12869
|View full text |Cite
|
Sign up to set email alerts
|

CCL2 promotes cell migration by inducing epithelial‐mesenchymal transition in oral squamous cell carcinoma

Abstract: Background Although a few studies suggested that the chemokine CCL2 might be involved in the development of oral squamous cell carcinoma (OSCC), the exact mechanism remains unclear. In this study, we aimed to determine the resource of CCL2 in lesions and explored a potential mechanism that CCL2 promotes tumor progression. The study was an effort to provide new insights into the pathological role of CCL2 in OSCC. Methods Specimens of OSCC and normal oral mucosa were stained using immunohistochemistry (IHC) to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…Interestingly, various chemokines have been implicated to contribute to EMT progression in cancer cells. EMT can be induced by CXCL8 and its receptors through overexpression of the transcription factor Brachyury [141], CCL2 with the enhancement of Snail expression [142], the CXCL6/CXCR1/2 axis via the PI3K/AKT and Wnt/β-catenin pathways [143], and the CXCL1/LCN2 paracrine axis with the activation of Src signalling [144]. In addition, NF-κB is associated with the EMT induced by CCL5 and CCL18 [145,146].…”
Section: Roles Of Chemokine System In Tumor Metastasismentioning
confidence: 99%
“…Interestingly, various chemokines have been implicated to contribute to EMT progression in cancer cells. EMT can be induced by CXCL8 and its receptors through overexpression of the transcription factor Brachyury [141], CCL2 with the enhancement of Snail expression [142], the CXCL6/CXCR1/2 axis via the PI3K/AKT and Wnt/β-catenin pathways [143], and the CXCL1/LCN2 paracrine axis with the activation of Src signalling [144]. In addition, NF-κB is associated with the EMT induced by CCL5 and CCL18 [145,146].…”
Section: Roles Of Chemokine System In Tumor Metastasismentioning
confidence: 99%
“…CCL2, a 13-kDa CC family of chemokines and also known as monocyte chemotactic protein-1 (MCP-1/CCL2), is produced mainly by monocytes/macrophages but is also expressed by endothelial, fibroblasts, epithelial, smooth muscle, mesangial, astrocytic, and microglial cells. Recently, Ling et al (2019) showed that oral squamous carcinoma cells can express and release CCL2 to effectively induce epithelial-mesenchymal transition. Moreover, there is a growing body of evidence that CCL2 has the ability to recruit monocytes and macrophages during development, inflammation, and tumorigenesis (Ferreira et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies will be required to evaluate the inflammatory response across racially divergent breast cancer cell lines or tissues. What we do know, however, is that compounds like apigenin that attenuate the CCL2/CCR2 axis would slow the aggressive nature of TNBC and hormone positive breast cancers (27,28) by attenuating invasion, metastasis, EMT and the development of drug resistance (59)(60)(61)(62). CCL2 inhibitors have been tested in various tumors, tumor cells and xenograft models with CCL2 lowering effects brought about by losartan (63) anlotinib (64) imatinib (65) zoledronic acid (66) oroxylin A (67) aspirin (68) natural compounds in coffee (kahweol acetate, cafestol) (69) or conophylline from Ervatamia microphylla (70) which can reduce invasive inflammatory tumor infiltration.…”
Section: Discussionmentioning
confidence: 99%